2020
DOI: 10.1007/978-1-0716-0592-9_20
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging of Cerebral Microhemorrhages and White Matter Degradation in Geriatric Patients with Mild Traumatic Brain Injury

Abstract: Traditionally, neurobiologists have utilized microscale techniques of scientific investigation to uncover the fundamental organization and function of brain cells and neuronal ensembles. In recent decades, however, macroscale brain imaging methods like magnetic resonance imaging (MRI) and computed tomography (CT) have facilitated a wider scope of understanding neural structure and function across the lifespan. Thanks to such methods, a broader picture of the relationship between microscale processesstudied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Vascular diseases can result in reductions in amyloid clearance and deposition, and hemorrhagic and ischemic changes can occur when amyloid acts on blood vessels [ 3 ]. Some previous studies have demonstrated that CMBs in patients with cognitive function decline may present several features of blood-brain barrier dysfunction [ 33 , 34 , 35 ]. A study on Tau proteins suggested that both Aβ and CSVD were independently associated with increased Tau accumulation and that Tau burden plays a pivotal role since it was the final common pathway for cognitive impairment in patients with subcortical vascular cognitive impairment [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular diseases can result in reductions in amyloid clearance and deposition, and hemorrhagic and ischemic changes can occur when amyloid acts on blood vessels [ 3 ]. Some previous studies have demonstrated that CMBs in patients with cognitive function decline may present several features of blood-brain barrier dysfunction [ 33 , 34 , 35 ]. A study on Tau proteins suggested that both Aβ and CSVD were independently associated with increased Tau accumulation and that Tau burden plays a pivotal role since it was the final common pathway for cognitive impairment in patients with subcortical vascular cognitive impairment [ 6 ].…”
Section: Discussionmentioning
confidence: 99%